Regulatory Roles of Bone in Neurodegenerative Diseases - Yu, Zhengran; Ling, Zemin; Lu, Lin; Zhao, Jin; Chen, Xiang; Xu, Pingyi; Zou, Xuenong (Frontiers in Aging Neuroscience, 2020)
Osteoporosis and neurodegenerative diseases are two kinds of common disorders of the elderly, which often co-occur. Previous studies have shown the skeletal and central nervous systems are closely related to pathophysiology. As the main structural scaffold of the body, the bone is also a reservoir for stem cells, a primary lymphoid organ, and an important endocrine organ. It can interact with the brain through various bone-derived cells, mostly the mesenchymal and hematopoietic stem cells (HSCs). The bone marrow is also a place for generating immune cells, which could greatly influence brain functions. Finally, the proteins secreted by bones (osteokines) also play important roles in the growth and function of the brain. This article reviews the latest research studying the impact of bone-derived cells, bone-controlled immune system, and bone-secreted proteins on the brain, and evaluates how these factors are implicated in the progress of neurodegenerative diseases and their potential use in the diagnosis and treatment of these diseases.